A study of the job description of library personnel of the College of Science Library, University of the Philippines Diliman - Gorospe, Ma. Judith Faye T.; Aguirre, Vyva Victoria M.; University of the Philippines (Diliman) College of Science Library (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2010)
Librarianship is a profession that is constantly changing. New tasks are emerging and other are becoming obsolete due to new technologies, which makes the importance of job descriptions emphasized now more than ever.
This is why a study on the job descriptions of the library personnel of the College of Science Library in the University of the Philippines Diliman was conducted. This study aims to know whether duties between professional librarians and non-librarians at the College of Science Library are clearly delineated by using provisions in Section 5, Article I of the Republic Act 9246, also known as the Philippine Librarianship Act of 2003 as a guide. The study was conducted by identifying the duties listed in the job descriptions of the library personnel and comparing them with the actual duties they perform as enumerated in their performance targets. Questionnaires were also prepared and interviews were conducted to supplement the data gathered through analysis of the documents.
The respondents of the study were both the professional librarians and the non- librarians at the College of Science Library in the University of the Philippines Diliman, including its two unit libraries, namely the Marine Science Institute Library and the National Institute of Geological Sciences Library. Seven librarians and 15 non-librarians were included in the study, including the Head Librarians of the three libraries.
The pertinent data obtained from the data analysis and supplemental interviews revealed that: (a) duties to be performed by both professional librarians and non-librarians in College of Science Library, MSI Library and NIGS Library are clearly delineated. The duties expected of them are communicated to them through the job descriptions provided by the UP Main LIbrary; (b) Although sharing of duties is common among professional librarians at the College of Science Library, they still perform the duties in their job descriptions; (c) Professional Librarians in the MSI and NIGS libraries do execute duties set forth in their job descriptions, although they tend to do tasks for their support staff; (d) The duties that non-librarians execute fully correspond with those listed in their job descriptions, thus they only perform duties expected of them; (e) duties performed by the library personnel conform to the duties provided in Republic Act. No. 9246.
Recommendations presented are (a) preparing job descriptions for the non-librarians of the College of Science Library and the support staff members of the MSI and NIGS Libraries; (b) updating the job description of the library personnel to ensure that unnecessary tasks are removed and emerging duties are added; (c) examining the job descriptions of all the positions to ensure that duties of professional librarians and non-librarians are clearly delineated; (d) ensuring that the duties in the job descriptions correspond with the knowledge and skills of the library personnel; (e) further studies regarding job descriptions should be done in the other library units in UP Diliman and in other types of libraries as well.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Employees -- Job descriptions; Library personnel management -- Philippines -- Quezon City